Permafrost evolution in a mountain catchment near Santiago de Chile. (August 2021) - Ruiz Pereira, S.; Marquardt, C.; Beriain, E.; Lambert, F.
Abstract: The Chilean Central Andes near Santiago are a semi-arid region with substantial frozen water reserves in their high altitude cryosphere. Millions of people depend on the Andean cryosphere for freshwater supply. Over the last sixty years, global warming has altered the mountains' water balance, as the temperature rose, precipitation decreased, and deglacierization exposed hundreds of square kilometers. The distribution of solid water stored in soil permafrost and the potential effects of climate change on it are unknown. Here, we map favorable spots for permafrost occurrence at the "Monos de Agua" catchment, Aconcagua basin at 33°S, between 3600 and 5100 m a.s.l.. We identify these "cold spots" based on ground surface temperature and incoming solar radiation between 2017 and 2019. We suggest that these locations currently present permafrost and frozen water might actually be there. We confirmed a body of frozen water at one of these cold spots using an electrical resistivity survey. Our mapping suggests that at least 15 ± 7% of the catchment's surface is underlain by permafrost. Permafrost occurrence begins around 3600 m a.s.l. with low probability and only at locations with favorable conditions of low exposure and isolation. Permafrost occurrence probability increases with altitude, with the largest fraction present above 4200 m a.s.l. Our results suggest that the permafrost area in this region will decrease between 13 and 87% by the end of the century under the future global warming RCP scenarios. This event represents new challenges for the hydrological memory and water security planning in the Chilean Central Andes. Highlights: We assessed mountain cryosphere elements within protected, water scarce areas. Permafrost occurrence was confirmed, and its distribution was mapped. A feedback between permafrost distribution and deglacierization is discussed. Permafrost evolution, current and future distribution upon warming is presented.